1992
DOI: 10.1046/j.1365-313x.1992.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

The promoter of the rice gene GOS2 is active in various different monocot tissues and binds rice nuclear factor ASF‐1

Abstract: Summary A single copy gene has been isolated, termed GOS2, from rice. Sequence comparison revealed highly similar genes in mammals and yeast, indicating that GOS2 encodes an evolutionary conserved protein. GOS2 mRNA was detected in all tissues examined. When the upstream region was translationally fused to the reporter gene gusA it was found to drive expression in a variety of rice tissues and in cell suspensions of other monocot species following introduction by particle bombardment. Therefore, the GOS2 promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…To enable the overexpression of the OsNAC10 genes in rice, their full-length cDNAs were isolated and linked to the RCc3 promoter (Xu et al, 1995) for rootspecific expression and to the GOS2 promoter (de Pater et al, 1992) for constitutive expression, thereby generating the constructs RCc3:OsNAC10 and GOS2: OsNAC10. These constructs were introduced into rice using Agrobacterium tumefaciens-mediated transformation (Hiei et al, 1994), which yielded 15 to 20 independent transgenic lines per construct.…”
Section: Identification Of Stress-inducible Rice Nac Domain Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…To enable the overexpression of the OsNAC10 genes in rice, their full-length cDNAs were isolated and linked to the RCc3 promoter (Xu et al, 1995) for rootspecific expression and to the GOS2 promoter (de Pater et al, 1992) for constitutive expression, thereby generating the constructs RCc3:OsNAC10 and GOS2: OsNAC10. These constructs were introduced into rice using Agrobacterium tumefaciens-mediated transformation (Hiei et al, 1994), which yielded 15 to 20 independent transgenic lines per construct.…”
Section: Identification Of Stress-inducible Rice Nac Domain Genesmentioning
confidence: 99%
“…Here, we report the role of OsNAC10, one of the effective members selected from the prescreening, in drought tolerance. Overexpression of OsNAC10 under the control of GOS2 (de Pater et al, 1992), a constitutive promoter, and RCc3 (Xu et al, 1995), a root-specific promoter, improved plant tolerance of transgenic rice to drought, high salinity, and low temperature during the vegetative stage of growth. In addition, RCc3:OsNAC10 plants showed significantly enhanced drought tolerance at the reproductive stage, with a grain yield increase of 25% to 42% over the controls under field drought conditions.…”
mentioning
confidence: 99%
“…The GOS2 (rice eukaryotic translation initiation factor1-like gene) promoter has been shown to drive expression throughout the whole plant body (de Pater et al, 1992), while the RCc3 (rice lipid transfer proteinlike gene) promoter does so in a root-specific manner (Xu et al, 1995). Fifty independent lines for each construct were generated, and to eliminate somaclonal variation, successive field selection of T1 to T4 plants (4 years) was performed to identify elite lines that grew normally, without stunting.…”
Section: Oserf71 Overexpression In Rice Roots Enhances Drought Resistmentioning
confidence: 99%
“…First, its sequence was verified by sequencing a full-length cDNA clone that was isolated from a rice cell suspension cDNA library using a PCRamplified probe corresponding to a partial Orysa; KRP1 cDNA sequence. To investigate the possible role of Orysa;KRP1 in rice development, we generated transgenic plants overexpressing the gene under the control of the constitutive rice GOS2 promoter (de Pater et al, 1992). Quantitative evaluation of transcript levels following transformation showed that the Orysa;KRP1 gene was overexpressed in all four independent transformation events analyzed (Supplemental Fig.…”
Section: Generation Of Orysa;krp1-overexpressing Linesmentioning
confidence: 99%
“…The Orysa;KRP1 cDNA was linked at its 5# end to the GOS2 promoter (de Pater et al, 1992) and at its 3# end to the ZEIN terminator (Wu et al, 1993).…”
Section: Generation Of Rice Krp1 Oe Transgenic Lines and Growth Condimentioning
confidence: 99%